White Matter Neurons in Young Adult and Aged Rhesus Monkey - Mortazavi, Farzad; Wang, Xiyue; Rosene, Douglas L.; Rockland, Kathleen S. (Frontiers in Neuroanatomy, 2016)
In humans and non-human primates (NHP), white matter neurons (WMNs) persist beyond early development. Their functional importance is largely unknown, but they have both corticothalamic and corticocortical connectivity and at least one subpopulation has been implicated in vascular regulation and sleep. Several other studies have reported that the density of WMNs in humans is altered in neuropathological or psychiatric conditions. The present investigation evaluates and compares the density of superficial and deep WMNs in frontal (FR), temporal (TE), and parietal (Par) association regions of four young adult and four aged male rhesus monkeys. A major aim was to determine whether there was age-related neuronal loss, as might be expected given the substantial age-related changes known to occur in the surrounding white matter environment. Neurons were visualized by immunocytochemistry for Neu-N in coronal tissue sections (30 μm thickness), and neuronal density was assessed by systematic random sampling. Per 0.16 mm2 sampling box, this yielded about 40 neurons in the superficial WM and 10 in the deep WM. Consistent with multiple studies of cell density in the cortical gray matter of normal brains, neither the superficial nor deep WM populations showed statistically significant age-related neuronal loss, although we observed a moderate decrease with age for the deep WMNs in the frontal region. Morphometric analyses, in contrast, showed significant age effects in soma size and circularity. In specific, superficial WMNs were larger in FR and Par WM regions of the young monkeys; but in the TE, these were larger in the older monkeys. An age effect was also observed for soma circularity: superficial WMNs were more circular in FR and Par of the older monkeys. This second, morphometric result raises the question of whether other age-related morphological, connectivity, or molecular changes occur in the WMNs. These could have multiple impacts, given the wide range of putative WMN functions and their involvement in both corticothalamic and corticocortical circuitry.